A method of sexing Moorhens - Anderson, A (Wildfowl, 1975)
A method of sexing Moorhens Gallinula chloropus in the hand was tried using discriminant analysis with three combinations of four body measurements taken from specimens sexed by dissection. The most reliable is length of tarsus + middle toe combined with culmen length, giving 88% of birds correctly sexed. Seasonal variation in the four standard measurements were examined in a marked population of Moorhens at Newburgh. Culmen length varies according to breeding cycle. Wing length can be affected by damage to wingtips during territorial display posturing. Moorhens lose weight from December to February and maximum weight of the female is at egg-laying. Tarsus + longest toe length does not vary once its full length is reached in sub-adulthood. Moorhens may be sexed by behaviour but reversed copulation sometimes occurs.